2013
DOI: 10.4049/jimmunol.1201212
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Mediated Innate Response and Adaptive Immune Cells Contribute to Maximum Responses of Protease Allergen–Induced Allergic Airway Inflammation

Abstract: How the innate and adaptive immune systems cooperate in the natural history of allergic diseases has been largely unknown. Plant-derived allergen, papain, and mite allergens, Der f 1 and Der p 1, belong to the same family of cysteine proteases. We examined the role of protease allergens in the induction of Ab production and airway inflammation after repeated intranasal administration without adjuvants and that in basophil/mast cell stimulation in vitro. Papain induced papain-specific IgE/IgG1 and lung eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(176 citation statements)
references
References 56 publications
10
164
0
2
Order By: Relevance
“…Thus, in experimental arterial hypertrophy mediated by Th2 immune responses, there are at least two pathways: T cell dependent and T cell independent. These pathways may cooperate with or compensate for each other to induce pulmonary arterial hypertrophy, as reported previously in allergic inflammation (41).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, in experimental arterial hypertrophy mediated by Th2 immune responses, there are at least two pathways: T cell dependent and T cell independent. These pathways may cooperate with or compensate for each other to induce pulmonary arterial hypertrophy, as reported previously in allergic inflammation (41).…”
Section: Discussionmentioning
confidence: 80%
“…Proteolytic activity of several allergens favours Th2 polarization and IgE responses [16,17,21]. Repeated exposure of airway mucosa with protease allergens leads to lung eosinophilia and higher IgE in a protease-dependent manner [22]. However, physiological targets of proteolytic allergens and the factors promoting allergic sensitization remain to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent data demonstrated that cutaneous sensitization of mice to the model allergen papain depended on mast cells and was independent from IL‐33 25. In contrast, inhalant sensitization to papain involved IL‐33 26. Along these lines, we speculate that distinct routes of sensitization involving different pathways, cell types and cytokines may also result in a different distribution of allergen‐specific Th subsets.…”
Section: Discussionmentioning
confidence: 66%